2020
DOI: 10.1186/s12935-020-01620-1
|View full text |Cite
|
Sign up to set email alerts
|

LINC00152 upregulates ZEB1 expression and enhances epithelial-mesenchymal transition and oxaliplatin resistance in esophageal cancer by interacting with EZH2

Abstract: Background Expression of the long non-coding mRNA LINC00152 has been reported to correlate with cancer cell resistance to oxaliplatin (L-OHP). However, little is known regarding the molecular mechanism of LINC00152 in esophageal cancer (EC). Hence, we intended to characterize the role of LINC00152 in EC, with a special focus on epithelial-mesenchymal transition (EMT) and L-OHP resistance. Methods We collected EC tissues and identified EC cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…Chen et al identi ed a novel metastasis-promoting lncRNA, MRPL23-AS1, which mediates the transcriptional silencing of E-cadherin by forming an RNA-protein complex with EZH2 [21]. EZH2 is also closely associated with the EMT of other tumors, such as pancreatic cancer, head and neck squamous cell carcinoma and esophageal cancer [22][23][24]. It has been reported that the EZH2 inhibitors MC4040 and MC404 reverse EMT and hamper cell migration and invasion, attenuating the glioma malignant phenotype [25].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al identi ed a novel metastasis-promoting lncRNA, MRPL23-AS1, which mediates the transcriptional silencing of E-cadherin by forming an RNA-protein complex with EZH2 [21]. EZH2 is also closely associated with the EMT of other tumors, such as pancreatic cancer, head and neck squamous cell carcinoma and esophageal cancer [22][23][24]. It has been reported that the EZH2 inhibitors MC4040 and MC404 reverse EMT and hamper cell migration and invasion, attenuating the glioma malignant phenotype [25].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, posttranslational modifications of PARP1, such as mono (ADP-ribosyl)-ation ( 36 , 37 ), phosphorylation, methylation, and acetylation, can modulate its activity. Thus, LINC00152 may influence PARP1 posttranslational modification by binding to the enhancer of zeste homologue 2 (EZH2) ( 38 ) or participate in the phosphatidylinositol 3-kinase/AKT signaling pathway ( 39 ), which may also be important for PARP1 expression and activity.…”
Section: Discussionmentioning
confidence: 99%
“…In multiple cancers, LINC00152 supports EMT and metastasis by positively regulating the level of ZEB1, PI3K, and AKT [ 166 , 167 ]. In gallbladder cancer, LINC00152 was also observed to exhibit EMT- and metastasis-promoting activities via sponging miR-138-5p that targets HIF-1α [ 146 ] ( Figure 2 and Table 2 ).…”
Section: Lncrnas Regulating Hif-1α Expressionmentioning
confidence: 99%